Keterampilan Komunikasi Interpersonal Guru dalam Pembelajaran Digital Berbasis Daring - Purnomo, Purnomo (Persatuan Guru Republik Indonesia Kota Semarang, 2023)
Teacher interpersonal communication skills play an important role in learning, but there have not been many studies on the applicability of these skills in online-based digital learning. This study aims to examine the concept of implementing interpersonal communication in online learning. This study uses the literature study method by referring to literature related to interpersonal communication, communication in learning, and online learning. This research shows that the implementation of interpersonal communication in online learning needs adjustments, including: 1. In online learning, teachers cannot be physically present but can be present socially, cognitively, and learning through scaffolding, direction, and focusing. 2. Teachers should emphasize the importance of quality of communication, not duration, by strengthening relationships and effective communication with students through increasing student involvement in decision-making, distributing roles for each student, and increasing the teacher's sensitivity to the dynamics of student feelings.